2008
DOI: 10.1089/jpm.2007.0241
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Falls in Patients with Cancer Hospitalized for Palliative Care

Abstract: Characteristics of falls in palliative care appear different from those evidenced in geriatric wards. To prevent delirium while prescribing neuroleptic drugs with the greatest caution should help decrease the number of falls in this highly vulnerable group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
3
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 31 publications
3
62
3
6
Order By: Relevance
“…Conversely, nonvalidated tools were used to measure alertness and confusion and subjective methods used to assess muscle strength; any resulting misclassification bias involving these ordinal variables may have resulted in an away from the null bias, i.e., suggesting an association between the variable and falls where none exists. 18 In the study by Pautex et al, 33 the charts of all patients with advanced cancer hospitalised over a one year period were reviewed and the characteristics of those who fell during admission compared to those who did not. In addition to those variables shown to be associated with falls, as per Table 2, the following variables were examined; demographic details, Charlson Comorbidity Index, main medical diagnoses, Mini-Mental State Examination (MMSE), functional independence measure, incident comorbidities, hemoglobin concentration, administration of opioid, benzodiazepine, neuroleptic, antiepileptic, antidepressant, hypotensive, diuretic, respiratory system, corticosteroid and antibiotic med- ications, use of parenteral hydration or nutrition, and administration of palliative sedation.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Conversely, nonvalidated tools were used to measure alertness and confusion and subjective methods used to assess muscle strength; any resulting misclassification bias involving these ordinal variables may have resulted in an away from the null bias, i.e., suggesting an association between the variable and falls where none exists. 18 In the study by Pautex et al, 33 the charts of all patients with advanced cancer hospitalised over a one year period were reviewed and the characteristics of those who fell during admission compared to those who did not. In addition to those variables shown to be associated with falls, as per Table 2, the following variables were examined; demographic details, Charlson Comorbidity Index, main medical diagnoses, Mini-Mental State Examination (MMSE), functional independence measure, incident comorbidities, hemoglobin concentration, administration of opioid, benzodiazepine, neuroleptic, antiepileptic, antidepressant, hypotensive, diuretic, respiratory system, corticosteroid and antibiotic med- ications, use of parenteral hydration or nutrition, and administration of palliative sedation.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Evidence has shown that cancer-related fatigue 24, 25 and pain 26, 27 influences functional status in elderly survivors increasing the risk of falls 28 . Some evidence suggests that people with cancer fall more often than others 810 and that certain types of cancer 29, 30 or metastatic disease 30 may be associated with higher rates of falling. Three studies conducted in palliative care settings demonstrating the incidence rate of falls to be significantly higher 81031 .…”
Section: Review Of Literaturementioning
confidence: 99%
“…Some evidence suggests that people with cancer fall more often than others 810 and that certain types of cancer 29, 30 or metastatic disease 30 may be associated with higher rates of falling. Three studies conducted in palliative care settings demonstrating the incidence rate of falls to be significantly higher 81031 . Both the rate of falls and risk of falling may be significantly higher for cancer survivors 8, 9 .…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations